Land use changes and sediment yield on a hilly watershed in Central-East Argentina - Delgado, María Isabel (2015)
Watershed management strategies need suitable techniques to be available in order to quantify sediment yield, among other relevant issues. The aim of this work was to estimate the sediment yield on a hilly watershed, for two different land use scenarios (years 1966 and 2011) and rainfall events (106 mm and 65.5 mm). The Modified Universal Soil Loss Equation was used to estimate the sediment yield produced by a single rainfall on the watershed of the Belisario Creek, placed south-west of the Buenos Aires province, Argentina. The information was processed using the Geographic Information System Idrisi Taiga®. Modelling the 45-year distant land use scenarios allowed to estimate the high level of degradation that is currently taking place on the watershed. Also, we detected different responses through different areas of the watershed; the same rainfall event in the 2011 land use scenario compared to the 1966 scenario showed a 400% increment in sediment yield in the upper sub-watersheds, together with an almost 100% increment near the sink. Here we propose the urgent need to elaborate a sustainable plan for the watershed of the Belisario Creek, in order to establish action criteria that could help improve natural resources management. The methodology used could be also applied to neighbouring watersheds with similar characteristics in the region.